Glocalizing tradition: Cultural diplomacy, craft education, and identity construction in Hatta Kabong’s weaving practices - Zuhro, Aida Roihana; Wahyono, Wahyono; Arianingsih, Arianingsih; Mahardhika, Cholis; Cahyandaru, Pramudya (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
This study examines the preservation of cultural identity amid modernization and globalization through the case of Hatta Kabong, a Belitung craftsman whose weaving and songket embody Malay identity. Despite their symbolic and economic value, these textiles face declining youth interest, artisan regeneration gaps, market competition, and tensions over commercialization. Previous studies largely discuss craft sustainability at the community or industry level, leaving limited analysis of how individual artisans strategically negotiate identity in changing socio-economic contexts. Addressing this gap, this research analyzes how tradition and modernity are reconciled through innovation, cultural diplomacy, and craft education. The study’s novelty lies in proposing an integrated identity-preservation model that links individual agency, cultural diplomacy, and educational transmission within a single analytical framework, thereby extending discussions of cultural sustainability beyond structural approaches. Using a qualitative case study, data were collected through participant observation, in-depth interviews, and documentation, and analyzed through systematic data reduction and interpretative categorization. The findings show that identity is sustained through design hybridization, institutionalized regeneration via Rumah Budaya Kabong, cross-ethnic participation, and international festivals as instruments of soft power, although efforts remain vulnerable to resistance and reliance on individual leadership. The study concludes that sustainable preservation requires balancing authenticity and innovation through institutional support and recommends integrating craft education into formal and informal curricula to strengthen intergenerational transmission and global competitiveness.